Lactose intolerance in irritable bowel syndrome patients with diarrhoea: the roles of anxiety, activation of the innate mucosal immune system and visceral sensitivity. Issue 3 (5th December 2013) - Yang, J.; Fox, M.; Cong, Y.; Chu, H.; Zheng, X.; Long, Y.; Fried, M.; Dai, N.
Summary Background Irritable bowel syndrome patients with diarrhoea (IBS‐D) often report intolerance to milk; however, the mechanism underlying these symptoms is unknown. Aim To assess the role of psychological factors, immune activation and visceral sensitivity on the development of lactose intolerance (LI) in IBS‐D patients. Methods Fifty‐five IBS‐D patients and 18 healthy controls (HCs) with lactase deficiency underwent a 20‐g lactose hydrogen breath test (LHBT). Patients were categorised as lactose malabsorption (LM; malabsorption only) or LI [malabsorption plus increase in total symptom score (TSS). Measurements included (i) psychological status; (ii) enteric biopsies with quantification of mast cells (MCs), T‐lymphocytes and enterochromaffin cells; (iii) serum cytokines; (iv) rectal sensitivity before and after lactose ingestion. Results LI was more prevalent in IBS‐D patients than HCs [25/55 (46%) vs. 3/18 (17%), P = 0.029]. IBS‐D patients with LI had (i) higher levels of anxiety than those with LM (P = 0.017) or HCs (P = 0.006); (ii) increased mucosal MCs compared with LM (P = 0.006) and HCs (P < 0.001); (iii) raised serum TNF‐α compared with LM (P = 0.034) and HCs (P < 0.001) and (iv) increased rectal sensitivity after lactose ingestion compared with LM (P < 0.001) or HCs (P < 0.001). Severity of abdominal symptoms after lactose ingestion was associated with the increase in visceral sensitivity after lactose intake (r = 0.629, P < 0.001), MCs (r = 0.650, P < 0.001) and anxiety (r = 0.519, P < 0.001). Conclusions IBS‐D patients with lactose intolerence are characterised by anxiety, mucosal immune activation and increased visceral sensitivity after lactose ingestion. The presence of these biomarkers may indicate an IBS phenotype that responds to dietary therapy and/or mast cell stabilisers (ClinicalTrials.gov Identifier: NCT01286597).